An investigation of teachers' perception of well-being under the conditions of COVID-19 in private (independent) high schools in the Cape Town Metro – a survey analysis. - Atkins, Candrine (School of Education, 2024)
Teachers, playing a pivotal role in education, are increasingly facing complex challenges, including addressing students' social and emotional needs, managing classrooms, integrating technology, and navigating evolving educational policies. These challenges, along with limited resources and societal expectations, can significantly impact teachers' well-being. This study investigated the impact of the COVID-19 pandemic on the well-being of private high school teachers in Cape Town, South Africa. Grounded in Carol Ryff's Scales of Psychological WellBeing, the research explores the multifaceted dimensions of teachers' psychological well-being in the context of unprecedented changes brought about by the global pandemic. A mixed methods approach combining quantitative and qualitative methods for a comprehensive understanding of well-being was used through a survey that targeted the selected private high schools in Cape Town. Purposive sampling was used to select six private high schools based on specific criteria. The sample (N) included 76 participants who fully completed the questionnaire and were therefore analysed. Data collection involved a survey with both closed-ended (quantitative: Likert scale) and open-ended (qualitative) questions, employing Ryff's psychological well-being model. The central aspects of Ryff's model refer to well-being along the categories of autonomy, environmental mastery, personal growth, positive relations, self-acceptance, and purpose in life. Where scores are high, along these dimensions, well-being is high. Findings in relation to this sample indicate that autonomy reveals a contradiction between high quantitative scores and qualitative struggles, particularly regarding curriculum constraints. While teachers indicate in the survey Likert scale quantitative data that they have high autonomy, in the open-ended questions they indicated a contradictory finding in relation to the curriculum, over which they felt little autonomy. Environmental Mastery, with the lowest average score, reflects challenges in managing uncertainties, especially during the pandemic. Personal growth scored the highest in this survey, indicating widespread positive perceptions of development despite challenges. Qualitatively the participants indicate that their ability to deal with the technological challenges they faced under COVID made them grow personally. Purpose in life sees a positive shift due to the pandemic, fostering personal growth and re-evaluation of life direction. Positive relations scores lower, emphasizing the complexity of interpersonal connections during challenges like online teaching, where face to face meetings are not possible. Finally, Self-acceptance scored positively, indicating teachers' positive attitudes toward continuous learning and selfdiscovery. Again, this can be attributed to teachers' perceptions that they met the technological challenges of online teaching during the pandemic. Overall, scores of well-being were high indicating that teachers in private schools were able to navigate the pandemic relatively well.